2017
DOI: 10.1186/s12913-016-1965-6
|View full text |Cite
|
Sign up to set email alerts
|

The treatment of non-malarial febrile illness in Papua New Guinea: findings from cross sectional and longitudinal studies of health worker practice

Abstract: BackgroundThe Papua New Guinea Department of Health recently shifted from a presumptive to a ‘test and treat’ malaria case management policy. This shift was supported by the widespread introduction of malaria rapid diagnostic tests in health facilities across the country. Health workers received training and job-aids detailing how to conduct and interpret a malaria rapid diagnostic test and how to treat test positive cases; however, little instruction on treating non-malaria febrile cases was provided. Accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…Additionally, patients in this study who were older were less likely to improve, and although non-communicable diseases are thought to be increasingly responsible for morbidity in older adults 11 , infectious disease remains a primary driver of illness in rural Malawi. Similar to other non-malarial fever studies, this study found that most non-malarial fevers were assigned a diagnosis of respiratory illness and the majority of patients were given analgesics, followed by antibiotics 12,13 . None of the adult patients in this study were given anti-malarials, unlike similar settings where providers may prescribe anti-malarials despite a negative mRDT 14 .…”
Section: Discussionsupporting
confidence: 78%
“…Additionally, patients in this study who were older were less likely to improve, and although non-communicable diseases are thought to be increasingly responsible for morbidity in older adults 11 , infectious disease remains a primary driver of illness in rural Malawi. Similar to other non-malarial fever studies, this study found that most non-malarial fevers were assigned a diagnosis of respiratory illness and the majority of patients were given analgesics, followed by antibiotics 12,13 . None of the adult patients in this study were given anti-malarials, unlike similar settings where providers may prescribe anti-malarials despite a negative mRDT 14 .…”
Section: Discussionsupporting
confidence: 78%
“…Health worker distrust of RDT negative results has been widely documented internationally [ 6 10 ] and is likely exacerbated by a dearth of cheap and reliable diagnostic point of care tests for other febrile illnesses [ 33 ]. In the absence of a reliable means of differential diagnosis, or intensive training to support differential diagnosis, then health workers may revert to a previous practice of clinically diagnosing malaria or they may adopt other ‘convenience’ diagnoses and prescription practices, as may already be evident by high rates of antibiotic prescription in RDT negative cases [ 34 36 ]. Adhering to RDT results has been proven safe in the PNG context [ 37 ], so the continued distrust suggests further clinical education is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…However, many NMFI patients are not receiving a more intensive or varied diagnostic examination (as may be expected following ‘the ruling out’ of malaria infection by RDT) and the rate of antibiotic prescription (83%) is alarmingly high. A recent study of health worker adherence to national prescription guidelines in PNG found antibiotics were overprescribed in 41% of over 3000 NMFI cases across 10 specified illnesses [ 25 ] and international evidence suggests antibiotic over prescription in NMFI is a growing concern [ 26 ]. Ensuring appropriate management of NMFI is increasingly important in PNG as malaria case positivity rates have dropped (often well) below fifty percent [ 27 ] in response to an effective national malaria control programme [ 17 ].…”
Section: Discussionmentioning
confidence: 99%